Morphometry and geographical variation of Bothriurus bonariensis (Scorpiones: Bothriuridae) - Olivero, Paola Andrea (2012)
Diversification of morphological characteristics among geographically separated populations is particularlyimportant in understanding evolutionary processes and is considered the early stage of allopatric speciation. In the presentstudy, we investigated geographic variation in scorpion populations of Bothriurus bonariensis (Koch 1842). Our principalgoal was to compare different populations of this species with regard to its distribution, analyzing somatic and genitaliccharacters. In Argentina, specimens of B. bonariensis from Entre Rios and Corrientes Provinces are dark brown, whilespecimens from La Pampa have reddish coloration. Scorpions of this species from Brazil and south of Uruguay are totallyblack. Also, we observed variability in body size, some morphological characteristics of adult specimens (e.g., prosomalength, hand height, hand width, and telson height), and genitalic traits (e.g., hemispermatophore lamina length, basal anddistal lamina width, dorsal fold length). Results indicate the presence of evident geographic variation: populations fromArgentina show similar morphological patterns that differ from populations from Uruguay. We discuss these data in thecontext of the current phylogeographical and evolutionary knowledge of this species.